The Legal Position of Waqf for Non-Muslims in Efforts to Increase Waqf Assets in Indonesia - Sulistiani, Siska Lis (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This study examines the legal standing of waqf for non-Muslims contributing to the increase of waqf assets in Indonesia. It turns out that raising waqf funds can be accessed from non-Muslim funds that sympathize with the economic value of Islamic philanthropy. Waqf is a deed that is part goodness of Islam and has a socioeconomic dimension. The essence of waqf is to hold the core of waqf and develop the outcome, so that waqf assets do not just disappear. The form of waqf is exciting and has great benefits so that not only a Muslim who is interested in waqf, many non-Muslims also contribute through donations. However, scholars differ in opinions about non-Muslim waqf laws; besides that, the waqf law also does not mention the specificity of waqf only for Muslims. This research is qualitative research through a normative juridical approach through literature in analyzing the data obtained. So, the difference in opinion of the madzhab scholars is essentially allowing non-Muslim endowments if it is not intended for religious facilities such as mosques.